Heat Transfer Efficiency Analysis and the Impact of Fouling Factor on Shell and Tube Heat Exchangers in Petroleum Processing - Fatimah Az Zahro; Mukasi Wahyu Kurniawati; Ani Purwanti (Jurnal Inovasi Teknologi, 2026)
Heat exchangers are essential equipment in petroleum processing, functioning to transfer heat between fluids to enhance process energy efficiency. Over extended periods of operation, the performance of these heat exchangers can decline significantly due to the formation of fouling on the heat transfer surfaces. This study aims to analyze the heat transfer efficiency and evaluate the impact of the fouling factor on a shell and tube heat exchanger (HE-05) operating in the crude oil refinery unit at PPSDM MIGAS Cepu. The research method employs a quantitative approach based on actual operational data obtained through direct field observations, including temperature data, flow rates, fluid densities, and equipment technical specifications. Performance evaluation was conducted by calculating the overall heat transfer coefficient, fouling factor, pressure drop, and thermal efficiency. The analysis results indicate that the overall heat transfer coefficient under clean conditions (Uc) was 4.65 Btu/ft².hr.°F, while under actual operating conditions (Ud), it decreased to 4.31 Btu/ft².hr.°F. The obtained fouling factor reached 0.0169 ft².hr.°F/Btu, exceeding the recommended minimum standard value, which indicates an accumulation of foulants. Nevertheless, the heat transfer efficiency of the equipment was recorded at 82.8%, which is classified as good and remains within the ideal efficiency range for shell and tube types. The pressure drop values on both the shell and tube sides were also confirmed to be far below the maximum allowable limits, suggesting that the equipment is still hydraulically suitable for operation. Based on these findings, scheduling periodic maintenance and cleaning is highly necessary to sustain the operational efficiency and performance of the heat exchanger